Behavior of LNG vapor clouds: tests to define the size, shape and structure of LNG vapor clouds - Meroney, Robert N., author; Neff, D. E., author; Kothari, K. M., author; Fluid Mechanics and Wind Engineering Program, Department of Civil Engineering, Colorado State University, publisher (Colorado State University. Libraries, 1980)
A terraced 1:240 scale model of the China Lake Naval Weapons Center was constructed to a resolution of one foot vertical increments and placed in the wind tunnel to determine the distances of lower flammability limit (LFL) for 1980, 40 cubic meter spills of Liquefied Natural Gas (LNG) under 4 wind speeds, 5 wind directions, and neutral flow conditions. A set of 8 aspirated hot-wire katharometer probes were made to determine the transient concentration at various downwind locations. Measurements of mean velocities, turbulence intensities, velocity spectra and correlations were performed over the model in the wind tunnel capable of simulating atmospheric phenomena. Data analysis has produced peak concentrations, contours of LFL, and time progressions of the plume ground level LFL. The wind tunnel test should determine the locations of meteorological or concentration instruments set up for field tests. In addition, the expected distances to LFL are determined by wind tunnel tests, thus the field program has the prior knowledge of the distances up to which the measurements should be performed.
Annual report for 1979-1980.
GRI 79/0073.
July 1980.
Keywords: Liquefied natural gas